Analisis Perbaikan Kualitas Layanan dengan Mengintegrasikan Model Kano – Quality Function Deployment (QFD) pada Jasa Perbankan (Studi Kasus: Bank BRI Unit Surian Kabupaten Solok) - Firman, Firman; Linda, Muthia Roza; Putri, Amelia Eka (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2016)
The purpose of this study was to analyze (1) the level of importance of each attribute of service quality in Bank BRI Unit Surian, (2) to analyze the performance of services in BRI Unit Surian, (3) to analyze the response techniques that prioritized for improvement service quality in Bank BRI Unit Surian.In this study, attributes are classified into Kano category and then integrated into the QFD using frameworks. The results showed there were eight attributes that are must-be category, nine attributes are one-dimensional, and 5 attributes are attractive. Based on the level of importance, the attributes considered most important by the customer is the bank provides personal attention to customers. While the attributes that have the highest performance values are employees who groomed, and attributes that have the lowest performance value is the bank's employees provide prompt service. Furthermore, the priority attribute is the bank keep accurate records. And priorities of technical responses is to provide standardized training services to employees.